Fractional Hermite-Hadamard inequalities containing generalized Mittag-Leffler function - Mihai, Marcela V (J Inequal Appl, 2017)
The objective of this paper is to establish some new refinements of fractional Hermite-Hadamard inequalities via a harmonically convex function with a kernel containing the generalized Mittag-Leffler function.